2018
DOI: 10.1039/c8ra07559j
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of immobilized tyrosinase – an enzyme that is stable in organic solvent at 100 °C

Abstract: Immobilized tyrosinase in hexane can withstand 100 °C over one week, and the half-life of the dry immobilized tyrosinase in organic solvent is strongly related to the polarity of the organic solvent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Examples of successful uses of TCO in optoelectronics are abundant, from well‐established state‐of‐the‐art devices such as silicon heterojunction solar cells and inorganic and organic light‐emitting diodes (LEDs) to perovskite solar cells (PSCs), and organic solar cells. [ 5–8 ] There are also many examples of TCOs in new approaches that simultaneously require semitransparency and flexibility, such as semitransparent conductors, field‐effect transistors, thermal shields, photo‐detectors, and vertical transistors. [ 9–14 ] PSCs have attracted much interest since their onset in 2009 due to rapidly‐increasing power conversion efficiencies (currently above 25% for small area cells).…”
Section: Introductionmentioning
confidence: 99%
“…Examples of successful uses of TCO in optoelectronics are abundant, from well‐established state‐of‐the‐art devices such as silicon heterojunction solar cells and inorganic and organic light‐emitting diodes (LEDs) to perovskite solar cells (PSCs), and organic solar cells. [ 5–8 ] There are also many examples of TCOs in new approaches that simultaneously require semitransparency and flexibility, such as semitransparent conductors, field‐effect transistors, thermal shields, photo‐detectors, and vertical transistors. [ 9–14 ] PSCs have attracted much interest since their onset in 2009 due to rapidly‐increasing power conversion efficiencies (currently above 25% for small area cells).…”
Section: Introductionmentioning
confidence: 99%
“…However, once a certain level is reached, the concentration of melanin begins to decline. This decline may be attributed to the inhibition of enzyme activity at high tyrosine concentrations, causing a decrease in melanin production (Wu et al 2018). The results suggest that the magnetic immobilized tyrosinase enzyme can effectively convert tyrosine to melanin, with the highest concentration obtained at a tyrosine concentration of 0.1.…”
Section: )mentioning
confidence: 99%
“…Tyrosinase has been immobilized on various carriers and its biocatalytic properties have been studied and compared to those of the free enzyme [ 25 , 26 , 27 , 28 , 29 ]; these studies showed that the immobilized form exhibits enhanced activity and stability. Cross-linking of enzyme molecules is another immobilization technique used for tyrosinase.…”
Section: Introductionmentioning
confidence: 99%